Recurrent mutation in the crystallin alpha A gene associated with inherited paediatric cataract. (December 2016) - Javadiyan, Shari; Craig, Jamie; Souzeau, Emmanuelle; Sharma, Shiwani; Lower, Karen; Pater, John; Casey, Theresa; Hodson, Trevor; Burdon, Kathryn
Abstract Background Cataract is a major cause of childhood blindness worldwide. The purpose of this study was to determine the genetic cause of paediatric cataract in a South Australian family with a bilateral lamellar paediatric cataract displaying variable phenotypes. Case presentation Fifty-one genes implicated in congenital cataract in human or mouse were sequenced in an affected individual from an Australian (Caucasian) family using a custom Ampliseq library on the Ion Torrent Personal Genome Machine. Reads were mapped against the human genome (hg19) and variants called with the Torrent Suite software. Variants were annotated to dbSNP 137 using Ion Reporter (IR 1.6.2) and were prioritised for validation if they were novel or rare and were predicted to be protein changing. We identified a previously reported oligomerization disrupting mutation, c.62G > A (p.R21Q), in the Crystallin alpha A (CRYAA ) gene segregating in this three generation family. No other novel or rare coding mutations were detected in the known cataract genes sequenced. Microsatellite markers were used to compare the haplotypes between the family reported here and a previously published family with the same segregating mutation. Haplotype analysis indicated a potential common ancestry between the two South Australian families with this mutation. The work strengthens the genotype-phenotype correlations between this functional mutation in the crystallin alpha A (CRYAA ) gene and paediatric cataract. Conclusion The p.R21Q mutation is the most likely cause of paediatric cataract in this family. The recurrence of this mutation in paediatric cataract families is likely due to a familial relationship.